Freeze-thaw stability of enzyme-treated sapin-sapin - Ronquillo, Angelique F.
ABSTRACT The objective of this study was to establish the stability of an enzyme-treated sapin-sapin exposed to sequential freeze-thaw cycles. Using the acceptable sapin-sapin formulation developed, the most suitable enzyme type and concentration was determined from treatments with α-amylases (0.005% and 0.012%) and pentosanases (0.003% and 0.005%) through evaluations of its physico-chemical and sensory characteristics. The most acceptable enzyme-treated sample was determined of its stability to freeze-thaw cycles by monitoring its changes through physico-chemical, microbiological tests and consumer acceptance tests for each cycle. The most acceptable sapin-sapin recipe was achieved by incorporating glutinous rice flour in a 2:1 proportion to rice flour in the David-Perez (1973) recipe and reducing the amount of coconut milk by 44%. Treatment of sapin-sapin with 0.012% α-amylase was found to be the most acceptable as it produced significantly better shape retention, increased stickiness and decreased chewiness of the product at a 5% level of significance. A significant increase in Aw and a significant decrease in firmness were also observed in the said treatment. With freeze-thaw cycles of control and amylase-treated samples, decreasing trends for syneresis and firmness and increasing trends for pH, Aw, and TPC were observed. Coliform counts and YMC were estimated to be below the detection limit of the technique used. Amylase-treated sapin-sapin was still acceptable until the 5th freeze-thaw cycle. Utilization of 0.012% α-amylase into sapin-sapin recipes was recommended for commercial production since it produced significant improvements in the textural qualities of sapin-sapin, enhanced its capacity to resist textural changes and was microbiologically safe for consumption until 5 cycles of freeze-thaw.